2014
DOI: 10.1159/000368751
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Developmental Speech Dysfluencies in Individuals with Parkinson's Disease

Abstract: Objective: The aim of this study was to investigate the incidence of developmental speech dysfluencies in individuals with Parkinson's disease (PD). Background: The possible relationship between PD and dysfluencies such as stuttering has engaged researchers for many years. However, whether there is a higher-than-expected incidence of reported childhood stuttering in adults with a diagnosis of PD is unknown. Participants and Methods: A questionnaire including items regarding present and former speech difficulti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 21 publications
1
13
1
Order By: Relevance
“…With respect to stuttering dysfluencies, the findings of this study indicated that individuals with PD presented a larger number of this type of disruption compared with those in the control group, corroborating abundant research found in the literature (1)(2)(3)(4)(5)(6)(7)(8)(9)16,(18)(19)(20)23) . Despite the consensus reported in the literature on the existence of stuttering-like dysfluencies in PD, the reasons for their occurrence are still controversial and not sufficiently clarified.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…With respect to stuttering dysfluencies, the findings of this study indicated that individuals with PD presented a larger number of this type of disruption compared with those in the control group, corroborating abundant research found in the literature (1)(2)(3)(4)(5)(6)(7)(8)(9)16,(18)(19)(20)23) . Despite the consensus reported in the literature on the existence of stuttering-like dysfluencies in PD, the reasons for their occurrence are still controversial and not sufficiently clarified.…”
Section: Discussionsupporting
confidence: 90%
“…The presence of dysfluencies in the speech of individuals with PD has been discussed in several studies in the specific scientific literature (1)(2)(3)(4)(5)(6)(7)(8)(9)16,(18)(19)(20)23) . The results of the present study corroborate the findings of a study (4) which reported that individuals with PD presented a larger number of stuttering-like dysfluencies and lower speech rate when compared with those of a control group.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations